2017
DOI: 10.18632/oncotarget.15147
|View full text |Cite
|
Sign up to set email alerts
|

SMYD2 lysine methyltransferase regulates leukemia cell growth and regeneration after genotoxic stress

Abstract: The molecular determinants governing escape of Acute Myeloid Leukemia (AML) cells from DNA damaging therapy remain poorly defined and account for therapy failures. To isolate genes responsible for leukemia cells regeneration following multiple challenges with irradiation we performed a genome-wide shRNA screen. Some of the isolated hits are known players in the DNA damage response (e.g. p53, CHK2), whereas other, e.g. SMYD2 lysine methyltransferase (KMT), remains uncharacterized in the AML context. Here we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 76 publications
2
21
0
Order By: Relevance
“…SMYD2 is directly activated by the transcription factor MYC, and ablation of SMYD2 impedes the development of leukemia promoted by the fusion oncogene MLL-AF9 [77]. In addition, SMYD2 knockdown confers relative resistance of human acute myeloid leukemia cells to multiple classes of DNA damaging agents, which is associated with the compensatory upregulation of SET7/9 [78]. Similarly, in chronic lymphocytic leukemia (CLL) patients, SMYD2 and SMYD3 are overexpressed, accompanied by a high white blood cell count and complex karyotype [79].…”
Section: Smyd2 In Cancermentioning
confidence: 99%
“…SMYD2 is directly activated by the transcription factor MYC, and ablation of SMYD2 impedes the development of leukemia promoted by the fusion oncogene MLL-AF9 [77]. In addition, SMYD2 knockdown confers relative resistance of human acute myeloid leukemia cells to multiple classes of DNA damaging agents, which is associated with the compensatory upregulation of SET7/9 [78]. Similarly, in chronic lymphocytic leukemia (CLL) patients, SMYD2 and SMYD3 are overexpressed, accompanied by a high white blood cell count and complex karyotype [79].…”
Section: Smyd2 In Cancermentioning
confidence: 99%
“…In two select cases, we performed targeted variant-to-function analyses to gain mechanistic insights into disease predisposition, starting with the missense variant in CHEK2. CHEK2 has been previously shown to modulate genotoxic responses in leukemia, but its role in primary human HSPCs had not been studied 40 . Importantly, the lead risk variant (I157T) in our study has been associated with increased risk for other cancers and shown to be a hypomorphic allele with functionally impaired activation of downstream effectors 41,42 .…”
Section: Main Textmentioning
confidence: 99%
“…Importantly, the lead risk variant (I157T) in our study has been associated with increased risk for other cancers and shown to be a hypomorphic allele with functionally impaired activation of downstream effectors 41,42 . Knowing this, we utilized previously characterized methods to suppress its activity or expression 40 . Consistent with observations made in leukemia cells, we found that CHEK2 inhibition reduced genotoxicity upon irradiation of primitive human Lin -CD34 + CD38cells, as compared to more differentiated progenitors (Extended Data Fig.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…SMYD2 was found to be a potential oncogene in the development of various tumors [ 11 ]. It was also reported that SMYD3 is involved in the invasion of cancer cells and is overexpressed in hepatocellular carcinoma and colorectal cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%